Pengaruh Perceived Value Pada Kepuasan Dan Loyalitas Nasabah Bank Mandiri Cabang WR Supratman - wiewiek indriani (Universitas Malahayati, 2012)
Abstract, Competition of the banking world is very competitive, therefore it takes maximum service tocreate customer satisfaction. This study aims to explain and prove the influence of the perceived valueby customer priority Bank Mandiri Branch WR Supratman to customer satisfaction and loyalty.Perceived value using three dimension that is functional value, emotional value and social value. Thisresearch use survey method by using purposive sample sampling method with 100 respondents ofcustomer priority Bank Mandiri WR Supratman which have fund equal to Rp 1 Billion up to Rp 10Billion. Data analysis method used in this research is regression analysis. The results indicate that 1)Perceived value has a positive and significant impact on customer satisfaction 2) Perceived value hasa positive and significant impact on customer loyalty 3) The influence of Customer SatisfactionAgainst Customer loyalty. The implication of this research is that the banking industry should payattention to its services because it affects the value received that impact on customer satisfaction andwill create loyal customers